BLAME ATTRIBUTION IN RAPE CRIMES: THE EFFECTS OF WILLING SUBSTANCE USE, RACE, AND RAPE MYTH ACCEPTANCE - Golubovic, Nedeljko (2017)
Rape is a highly prevalent crime, and it is one of the most severe traumatic events experienced by women. Previous researchers have found that, unlike other crimes, blame attribution in rape cases is inconsistent and influenced by many external elements (Bieneck & Krahe, 2011; Grubb & Turner, 2012; Masser, Lee, & McKimmie, 2010; Stewart & Jacquin, 2010). In this study, the influence of willing substance use and race on attribution of blame from a sample of 316 undergraduate students attending a large, Southeastern, public, urban university was examined. More specifically, results from this investigation described how the type of substance (alcohol, marijuana, and heroin) consumed by female survivors and survivors’ race/ethnicity (Black, Hispanic, and White) influenced the level of blame assigned to them. Additionally, the researcher explored the interactive effect of the drug type and survivors’ race. The results of the analysis of variance (ANOVA) revealed that both survivors’ substance use and race significantly influenced blame attribution. Survivors who consumed alcohol prior to the assault were blamed more than survivors who used heroin or marijuana and survivors who did not consume any substances. Regarding the influence of survivors’ race/ethnicity, White female survivors were attributed significantly higher levels of blame than Black and Hispanic female survivors. In addition to the examined conditions of substance use and race/ethnicity, the results of this study indicated that observers’ demographic characteristics influenced blame attribution as well. Observers’ gender, race, and knowledge of a person who has survived rape were all significant factors effecting attribution of blame